Effects of Fly Ash and Foundry Sand on Performance of Architectural Precast Concrete - Naik, Tarun R.; Kraus, Rudolph N.; Ramme, Bruce W.; Canpolat, Fethullah (ASCE-AMER SOC CIVIL ENGINEERS, 2012)
This research was conducted to establish the effects of fly ash and used foundry sand on strength and durability of concrete. Two series (Series 1 and Series 2) of experiments were performed. All concrete mixtures were produced for and at the production plant of an architectural precast concrete products producer. Concrete mixtures produced were used in manufacture of precast concrete panels. Tests were performed with normal and air-entrained fly ash concrete. Concrete test specimens were evaluated for compressive strength, abrasion resistance, salt-scaling resistance, freezing and thawing resistance, and chloride-ion penetration resistance. On the basis of strength and durability evaluations, it was concluded that both nonair and air-entrained concrete mixtures developed in this investigation are appropriate for manufacture of high-quality, high-durability architectural precast concrete using used foundry sand and fly ash. DOI: 10.1061/(ASCE)MT.1943-5533.0000432. (C) 2012 American Society of Civil Engineers.
Keywords: Compressive strength; Concrete; Durability; Fly ash; Sand; Precast concrete; FLOWABLE SLURRY; Construction & Building Technology; Engineering; Materials Science